2021
DOI: 10.16984/saufenbilder.793333
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Genetic Programming: Popular Techniques, Fundamental Aspects, Software Tools and Applications

Abstract: Genetic Programming (GP) is one of the evolutionary computation (EC) methods followed with great interest by many researchers. When GP first appeared, it has become a popular computational intelligence method because of its successful applications and its potentials to find effective solutions for difficult practical problems of many different disciplines. With the use of GP in a wide variety of areas, numerous variants of GP methods have emerged to provide more effective solutions for computation problems of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 156 publications
0
3
0
Order By: Relevance
“…In standard function, robot vision is utilized for part identification and navigation. In advanced function, the vision enables to lead and guide the robots or other automated machines to recognize, think and perform the task, resembling a human [11,12]. By controlling the special machine vision software, it can make the part identification and replace or complement manual inspections, navigation and measurements with digital cameras and imaging processes.…”
Section: B Robotics Visionmentioning
confidence: 99%
“…In standard function, robot vision is utilized for part identification and navigation. In advanced function, the vision enables to lead and guide the robots or other automated machines to recognize, think and perform the task, resembling a human [11,12]. By controlling the special machine vision software, it can make the part identification and replace or complement manual inspections, navigation and measurements with digital cameras and imaging processes.…”
Section: B Robotics Visionmentioning
confidence: 99%
“…Garcia-et al used decision trees(DT) that were generated by GP in order to detect primary financial incident changes (Garcia-Almanza and Tsang 2006). In recent work, Ari et al discussed use of an ensemble average GP model to represent stock exchange market trend based on other international market data (Ari and Alagoz 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the current work, authors have preferred an evolutionary hyper-parameter optimization technique to increase the accuracy of GP based stock market trend prediction models. In the previous work, authors demonstrated extracting a regression model of ISE100 index stock market by using ensemble average GP modeling method (Ari and Alagoz 2021). However, this approach cannot yield effective modeling for solutions of the day-ahead forecast problem.…”
Section: Hyper-parameter Optimizationmentioning
confidence: 99%